Mechanistic insight into the antidiabetic effects of Ficus hispida fruits: Inhibition of intestinal glucose absorption and pancreatic beta-cell apoptosis - Nusaiba Jahan; Noimul Hasan Siddiquee; Rifayat Ara Khanom Riva; Nur Uddin Chowdhury; Marjanur Rahman Bhuiyan; Khondoker Shahin Ahmed; Hemayet Hossain; Sadikur Rahman Shuvo; AFM. Shahid Ud Daula (PLoS ONE, 2025)
The worldwide health impact of Type 2 diabetes mellitus (T2DM) is marked by the dysregulation of glucose metabolism caused by α-glucosidase-mediated carbohydrate degradation and pancreatic β-cell apoptosis through caspase-3 activation. This study aimed to thoroughly investigate the potential roles and mechanisms of Ficus hispida fruits methanolic extract (FhME) and its phytoconstituents in combating T2DM by experimental and computational methods. In-vitro investigations demonstrated that, FhME exhibited notable α-glucosidase inhibitory activity compared to acarbose, as indicated by its low IC 50 value of 850 µg/mL. Furthermore, phytochemical analysis of FhME using the HPLC-DAD technique, combined with a review of previous literature, identified and quantified a total of 26 polyphenolic compounds. The network pharmacological investigation of FhME phytoconstituents identified 70 target genes associated with T2DM, where caspase-3 emerged as a key target. GO enrichment analysis, conducted using SRplot, highlighted key pathways, including apoptosis, lipid and atherosclerosis, and chemical carcinogenesis-receptor activation. Subsequently, molecular docking of caspase-3 with phytochemicals demonstrated strong binding affinity. Post-docking MM-GBSA study identified alpinumisoflavone and chlorogenic acid as exceptionally stable compounds. Molecular dynamics simulations conducted over 200 ns demonstrated that gallic acid and alpinumisoflavone produced the most stable complexes with caspase-3. These findings designate F. hispida fruits as a potential natural medicinal agent for Type 2 diabetes treatment, functioning through dual mechanisms of α-glucosidase inhibition and caspase-3 modulation of the apoptotic signaling pathway of the beta cells.